The development of the mammalian outer and middle ear. Issue 2 (30th July 2015) - Anthwal, Neal; Thompson, Hannah
Abstract: The mammalian ear is a complex structure divided into three main parts: the outer; middle; and inner ear. These parts are formed from all three germ layers and neural crest cells, which have to integrate successfully in order to form a fully functioning organ of hearing. Any defect in development of the outer and middle ear leads to conductive hearing loss, while defects in the inner ear can lead to sensorineural hearing loss. This review focuses on the development of the parts of the ear involved with sound transduction into the inner ear, and the parts largely ignored in the world of hearing research: the outer and middle ear. The published data on the embryonic origin, signalling, genetic control, development and timing of the mammalian middle and outer ear are reviewed here along with new data showing the Eustachian tube cartilage is of dual embryonic origin. The embryonic origin of some of these structures has only recently been uncovered ( Science, 339, 2013, 1453; Development, 140, 2013, 4386), while the molecular mechanisms controlling the growth, structure and integration of many outer and middle ear components are hardly known. The genetic analysis of outer and middle ear development is rather limited, with a small number of genes often affecting either more than one part of the ear or having only very small effects on development. This review therefore highlights the necessity for further research into the development of outer and middle ear structures, which will be important for the understanding and treatment of conductive hearing loss.